Fairfield, Neb., Comp. Ordinances no. 20, § 1 (1899) - (:unkn) unknown (My University, 1899)
An Ordinance to Prohibit the Carrying of Concealed Weapons and Fixing a Penalty for the violations of the same. Be it ordained by the Mayor and Council of the City of Fairfield, Nebraska: Prohibited the carrying of a concealed pistol, revolver, dirk, Bowie knife, billy, slingshot, metal knuckles, or other dangerous or deadly weapons. Punishable by forfeiture and "shall be so adjudged."
Keywords: CARRY - CONCEALED